EFFECT MINIMUM TILLAGE, CROP ROTATION AND CROP RESIDUES AS MANAGEMENT PRACTICES ON SOIL HEALTH - Al-Furaiji , H. T. R.; Ali , N. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
Two field experiments were conducted at the research station of College of Agricultural Engineering Sciences -University of Baghdad at Aljadriya, Baghdad –Iraq during two seasons 2021-2022, to evaluate effect of minimum tillage, crop rotation and crop residues on soil health. The 1st one was with split-plot arrangement with two factors: crop residues (0% Residues (0%R) and 100% Residues (100%R)) and tillage (minimum (MT) and conventional (CT)) with four replicates. The 2nd one was with split-split plot arrangement with three factors: the same tillage and residues in 1st trail coupled with crop rotation (clover – maize and clover – mung bean). Soil organic carbon (SOC), organic matter (SOM), active carbon (SAC), aggregate stability, EC, total bacteria and fungi count, available N, P, K, Fe, Zn were evaluated as a soil health indicators. Results of both trails indicated that the best results were (12.78 g SOC Kg-1, 22.03 g SOM Kg-1, 178.92 mg SAC Kg-1, 44.72%, 1.11 dS m-1, 425.0*108 CFU g-1 soil, 357.5*103 CFU g-1 soil, 50.75 mg N, 17.12 mg P, 279.9 mg K, 4.68 mg Fe Kg-1, 2.79 mg Zn Kg-1 soil for the treatment (100%R+MT+ clover – mung bean crop rotation) compared with results of (8.96 g SOC Kg-1, 15.45 g SOM Kg-1, 109.3 mg SAC Kg-1, 31.42% , 1.66 dS m-1, 33.5*108 CFU bacteria g-1 soil, 16.5*103 CFU fungi g-1 soil , 30.62 mg N, 11.75 mg P, 133.5 mg K, 2.95 mg Fe Kg-1, 1.73 mg Zn Kg-1 soil) for treatment (0%R+ CT+ without crop rotation ) respectively.